Analisis Pengaruh Kekuasaan dan Kemampuan Individu Anggota Tim (Studi Pada Pengaruh Keputusan Pembelian Batubara di Indonesia) (Jurnal Manajemen dan Kewirausahaan, 2010)
Research on “organizational purchase behavior” is less developed compared to research on “consumer purchase behavior” due to the difficulty to get data from industries and organizational purchase behavior is influenced by more factors than consumer purchase behavior. Because of these reasons not many people willing to take a research on organizational purchase behavior. Some researchers who have studied organizational purchase behavior, most of them only emphasize on: purchase process, department influence, organizational size and organizational structure. Only few of them who studied interpersonal process especially in the area of “power” owned by individual members of buying center in the company. Latent power is the important key that can control and influence to other member team of buying center to agree with his or her decision. This research is using 188 respondents of buying center from 30 Indonesian coal buying companies, such as: Power Plant, Cement Plant, Paper Plant and Trader company. This research are use clustering and regression technique. Clustering technique is used to grouped the research objects and identify the characteristics of each object. Regression method is used to identify which power is the most dominant to influence the purchase decision on buying center. The result on this study are: Indonesian coal purchaser based on the buying center characteristics, situational characteristics and individual behavior: can be divided to be five cluster, such as: (1) high familiarity & viscidity, (2) high consideration to government regulation, (3) high risk, (4) small member size and high influence attempt and (5) high time pressure. Using the regression technique on each cluster, can be identified the strongest power that influence to the buying center, there are: cluster 1: ability on management power, cluster 2: reinforcement power, cluster 3: ability on engineering power, cluster 4: reinforcement power and cluster 5: reinforcement power.